The ins and outs of drug-releasing vaginal rings: a literature review of expulsions and removals. (1st November 2020) - Boyd, Peter; Merkatz, Ruth; Variano, Bruce; Malcolm, R. Karl
ABSTRACT: Introduction: There is considerable interest in vaginal ring technology for sustained/controlled administration of drugs to the human vagina. Seven drug-releasing vaginal rings have reached market and other experimental devices are in preclinical/clinical development. Although most women who have used rings are satisfied and find them acceptable, involuntary expulsions and voluntary removals are known to occur and are widely reported. There have been no previous efforts to review this topic and understand the factors contributing to expulsions. Areas covered: This article will help researchers, clinicians and product developers better understand the pertinent factors and issues around ring expulsions and removals, and inform new research aimed at optimizing ring product design. The review contains four sections: (i) introduction to vaginal ring technology; (ii) discussion of the anatomical, physiological, device, and user factors affecting ring expulsion; (iii) review of involuntary expulsions; (iv) review of voluntary removals; and (v) concluding remarks/opinions. Expert opinion: Further research is needed to better understand the factors contributing to involuntary ring expulsions and removals so that rings can be better designed to minimize rates of expulsion and to reduce removals. Determination of optimum ring dimensions and stiffness are likely key factors, alongside better counseling around removal and reinsertion.